A CULTURAL HISTORY OF IMPERIAL CIVIL EXAMINATION TO CONTEMPORARY CHINESE EXAMINATION - KAI, Chen (Studia Universitatis Babeș-Bolyai Philologia, 2020)
A Cultural History of Imperial Civil Examination to Contemporary Chinese Examination. Examination is an evaluation to check if students understand the lessons as well as a stimulating method to help students have progress efficiently. With the long history of imperial civil examination, Chinese examination in modern society is of rigorousness and high-difficulty, and exam-oriented education is very popular. Examination system with influence from imperial civil examination has its advantages and disadvantages, and Chinese language examination designed by Chinese teachers with Chinese exam features is not very welcomed by foreign students. This paper is to have a comprehensive understanding of imperial civil examination in view of its development, its relationship with Confucianism and its influence to contemporary Chinese language education. With the comparison of attitudes to exam, exam function, question design between Chinese exam and Romanian exam, we can make use of the advantages of various exam mechanisms to improve students’ language level, knowledge of culture, and dialectic thinking. REZUMAT. O istorie culturală de la examinarea civilă imperială şi până la examinarea chinezească contemporană. Examinarea este o evaluare al cărei scop este acela de a verifica dacă studenţii au înţeles lecţiile predate, dar, în acelaşi timp, reprezintă şi o metodă stimulatoare, care îi ajută pe studenţi să cunoască un rapid progress. Având în spate istoria îndelungată a examinării civile imperiale, examinarea chinezească din societatea modernă este una riguroasă şi extrem de dificilă, educaţia orientată spre examinare fiind foarte populară în prezent. Acest sistem de examinare derivat din examinarea civilă imperială are avantajele şi dezavantajele sale, examinarea nivelului de cunoaştere a limbii chineze gândit de profesorii chinezi, potrivit specificului examenelor chinezeşti, nefiind foarte apreciată de studenţii străini. Acest articol îşi propune să ofere o înţelegere comprehensivă a examinării civile imperiale de-a lungul etapelor sale de dezvoltare, relaţiei cu sistemul filosofic confucianist precum şi influenţa sa asupra studierii limbii chineze contemporane. Comparând atitudinea faţă de examinare, funcţia şi structura examinării în sistemul de educaţie chinezesc şi românesc, se pot folosi avantajele cunoaşterii mai multor mecanisme de examinare, cu scopul de a îmbunătăţi nivelul de limbă, cultură şi gândire dialectică al studenţilor. Cuvinte cheie: examinarea civilă imperial, Confucianism, educaţie contemporană.